2015
DOI: 10.1007/s00520-015-2680-2
|View full text |Cite
|
Sign up to set email alerts
|

Exercise compliance among patients with multiple myeloma undergoing chemotherapy: a retrospective study

Abstract: In this sample of MM patients, high compliance with exercise and associated improvements in fatigue were observed. However, participants with a history of pathological fracture, SCC, or radiation are at increased risk of noncompliance and may require additional supervision to improve exercise compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 36 publications
1
39
0
Order By: Relevance
“…Physical exercise is considered an essential factor for improving cancer survival. Previous studies have indicated that exercise interventions are efficacious in men with prostate cancer (41,42) and in multiple myeloma (43,44). In endometrial, ovarian and colorectal cancer survivors, lifestyle interventions that include regular participation in physical activity are associated with positive health outcomes (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Physical exercise is considered an essential factor for improving cancer survival. Previous studies have indicated that exercise interventions are efficacious in men with prostate cancer (41,42) and in multiple myeloma (43,44). In endometrial, ovarian and colorectal cancer survivors, lifestyle interventions that include regular participation in physical activity are associated with positive health outcomes (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Commonly reported barriers to physical activity are pain, fear of fracture risk, lack of confidence and fatigue (Groeneveldt et al, 2013). Although more high quality randomised control trials (RCTs) are required in myeloma patients to determine efficacy (Gan et al, 2016;Smith et al, 2015), exercise training has been shown to be safe and feasible (Groeneveldt et al, 2013), with high attendance and adherence (Groeneveld et al, 2013;Shallwani et al, 2015) and higher physical activity levels have been associated with better quality of life both during and off active treatment (Jones et al, 2004;Groeneveld et al, 2013). Rehabilitation in myeloma patients after HSCT improves physical performance, muscle strength, aerobic capacity and immunological function; reduces fatigue and improves psychological outcomes (Groeneveldt et al, 2013;Persoon et al, 2013).…”
Section: Physical Fitness and Functionalitymentioning
confidence: 99%
“…Within the period of interest for our analysis, 39.4% of patients with bone metastasis exercised at the Wellness Centre and an additional 26% were given home programs. In our previously summarized studies, patients with spinal metastases were successfully treated with low-level cardiovascular and resistance training, improving their quality of life despite advanced cancer 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…To identify factors that contribute to compliance versus noncompliance with our model of exercise prescription, we retrospectively conducted, in 2014, a review of 41 patients with multiple myeloma 34 . Despite the fact that 81% of the patients had bone lesions and were undergoing active treatment, overall compliance with exercise prescription was 71%, mean levels of physical activity increased significantly (p < 0.001), and fatigue severity was reduced (p = 0.003).…”
Section: Select Population Outcomesmentioning
confidence: 99%